Analisis Biaya dan Manfaat Berbagai Skema untuk Pelayanan Hemodialisis di Rumah Sakit DR. Sitanala Tangerang - Nasron Azizan; Sutoto; Mary S. Maryam (JRB-Jurnal Riset Bisnis, 2020)
This research was conducted to review the clinical pathway and the calculation of total cost of hemodialysis services and to see the comparison of cost and benefits of hemodialysis services with the Operational Cooperation system and self-management in RSK DR Sitanala Tangerang in 2017 from 3 (three) Hemodialysis Machine Providers. The total cost of hemodialysis services with the Operational Cooperation system and self-management is the result of direct and indirect cost calculation with a combination of Activity Based Costing (ABC) methods in accordance with outpatient clinical pathways. Total Cost is obtained by summing the multiplication results between each activity cost in the period of 18 months. Revenue is obtained by summing the multiplication of hospital rates to the number of actions or visits of patients in 18 months. The result of the analysis of the benefits of hemodialysis costs turns out that the Operational Cooperation system is more profitable than self-managed.